2016
DOI: 10.1242/dev.137281
|View full text |Cite
|
Sign up to set email alerts
|

The Ets protein pointed prevents both premature differentiation and dedifferentiation of Drosophila intermediate neural progenitors

Abstract: Intermediate neural progenitors (INPs) need to avoid both dedifferentiation and differentiation during neurogenesis, but the underlying mechanisms are not well understood. In Drosophila, the Ets protein Pointed P1 (PntP1) is required to generate INPs from type II neuroblasts. Here, we investigated how PntP1 promotes INP generation. By generating pntP1-specific mutants and using RNAi knockdown, we show that the loss of PntP1 leads to both an increase in type II neuroblast number and the elimination of INPs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 43 publications
4
43
0
Order By: Relevance
“…First, PntP1 is specifically expressed in type II neuroblasts and in Ase − immature INPs (Figure 1A). Second, loss of pntP1 function leads to reduced Erm expression in immature INPs as well as supernumerary type II neuroblast formation (Komori et al, 2014a; Xie et al, 2016). Indeed, we found that knocking down pntP1 function reduced the expression of 9D11 2-5 -GFP in vivo , and the ETS-domain of PntP1 bound five of the seven putative PntP1-binding sites in the 9D11 2-5 enhancer in vitro (Figure 3J; Supplementary Figures 3H-I).…”
Section: Resultsmentioning
confidence: 99%
“…First, PntP1 is specifically expressed in type II neuroblasts and in Ase − immature INPs (Figure 1A). Second, loss of pntP1 function leads to reduced Erm expression in immature INPs as well as supernumerary type II neuroblast formation (Komori et al, 2014a; Xie et al, 2016). Indeed, we found that knocking down pntP1 function reduced the expression of 9D11 2-5 -GFP in vivo , and the ETS-domain of PntP1 bound five of the seven putative PntP1-binding sites in the 9D11 2-5 enhancer in vitro (Figure 3J; Supplementary Figures 3H-I).…”
Section: Resultsmentioning
confidence: 99%
“…PntP1 is expressed in type II NBs and imINPs to specify type II NBs and promote the generation of INPs by preventing both the dedifferentiation and premature differentiation of INPs (Xie et al, 2016; Zhu et al, 2011). Erm is normally activated by PntP1 only in imINPs, in which Notch is turned off (Koe et al, 2014; Xie et al, 2016). In the absence of Notch or its downstream E(spl) proteins, PntP1 activates erm in type II NBs.…”
Section: Introductionmentioning
confidence: 99%
“…The other possibility is that PntP1 functions in concert with another transcription factor leading to repression of Ase expression in type II NBs. In support of the latter, PntP1 was shown to genetically interact with the transcription factor Buttonhead (Btd), as halving the dosage of btd in pnt mutant background led to an increase in the number of Ase expressing type II NBs (Xie et al, , ). This suggests that PntP1 and Btd function together to inhibit Ase expression in type II NBs.…”
Section: Role Of Pointed During Drosophila Developmentmentioning
confidence: 99%
“…Intestinal stem cell proliferation P1, P2 Yes (Jin et al, 2015;Ren et al, 2013) Renal and nephric stem cells P1 Yes (Li, Liu, & Cai, 2015) Female germline stem cell niche (Liu, Lim, & Cai, 2010) Neural stem cell (Xie et al, 2014(Xie et al, , 2016Zhu, Barshow, Wildonger, Jan, & Jan, 2011) Tracheal branching Patterning the ventral ectoderm P1 Yes (Gabay et al, 1996;Golembo, Yarnitzky, Volk, & Shilo, 1999) Wing development P2 Yes (Paul et al, 2013) to directly regulate the expression of loco, which codes for an RGS domain containing protein that is required for ensheathment of longitudinal connectives and maintaining the integrity of the blood-brain barrier Granderath et al, 2000;Yuasa et al, 2003). As mutations in pnt affect glial cell differentiation, migration and ensheathment of commissural and longitudinal axons, considerable effort should be placed on identifying the downstream transcriptional targets genes that they activate in order to gain insight into how these processes are regulated.…”
Section: Stem Cellsmentioning
confidence: 99%